Motores lineares e suas aplicações : trens de levitação magnética - (:unkn) unknown (Universidade Federal do Pampa, 2026)
Since the advent of primitive electric motors by Michael Faraday in the 19th century, this class of devices has played a fundamental role in industrial, technological, and social development, being used in countless applications to convert electrical energy into mechanical energy. Among the various types of electric motors, linear electric motors stand out because they produce motion directly along a linear axis, eliminating the need for intermediate mechanisms and reducing losses due to friction and wear. This characteristic makes linear motors efficient and attractive options for a wide range of technological applications. In this context, this study aims to understand the operating principles of linear motors and analyze their applications, particularly those intended for transportation via magnetic levitation (Maglev) trains. Fundamental concepts of electromagnetism are addressed, considering the architecture of conventional and linear electric motors, as well as concepts of electromagnetic levitation and electrodynamics. Special mention is made of the design characteristics of Maglevs, including levitation, guidance, propulsion, and power supply. Examples and real-world projects developed and implemented in other countries such as Germany, Japan, the United States, Switzerland, and Brazil are also presented, highlighting their specific features and prospects for application. This study highlights the potential of magnetic levitation trains as an advanced and efficient alternative for the future of transportation, particularly for passenger transport, and especially given the growing demand for mobility systems with low energy, environmental, and social impacts. A literature review employing both qualitative and quantitative approaches was conducted, and a basic virtual experimental procedure with an exploratory objective was also performed.
Keywords: Motor elétrico; Motor elétrico linear; Levitação magnética; Trens de levitação magnética; Mobilidade elétrica; Electric motor; Linear electric motor; Magnetic levitation; Magnetic levitation trains; Electric mobility; ENGENHARIAS